Die rol van die ouerhuis in die intergenerasionele geloofsvorming van die jeug in belang van ’n geïntegreerde jeugbediening - Johan C. Avenant; Malan Nel; Joyce C. Jordaan (Verbum et Ecclesia, 2021)
The role of the parental home in the intergenerational faith formation of the youth for the sake of an integrated youth ministry. This article deals with the following question: What is the role of parents in the intergenerational faith formation of the youth for the sake of an integrated youth ministry? Several studies nationally and internationally have convincingly pointed out that parents have the biggest influence on their children’s faith formation. However, parents are currently still not sufficiently inclusively involved or supported in youth ministry. Osmer’s fourfold reflective equilibrium model forms the frame for how this article is structured. Nel’s theory of inclusive youth ministry is used as a theological framework from which the role of parents in intergenerational faith formation is investigated. The empirical research (quantitative, as well qualitative) was conducted among 175 parents and 10 ministers coming from 29 congregations in the Noordelike, Oostelike, Hoëveld- and Goudland synods of the Dutch Reformed Church. These congregations all have a family and/or intergenerational focus in their (youth) ministry. The research has shown that youth ministry cannot by means of programmes, structures and even relationships in any way replace the important role played by parents in the lives of their children, regardless of what happens in the youth ministry. When the parental home and youth ministries do not act as partners in the faith formation process, it does not only lead to weak faith, but also to a lack of commitment, unsustainability and ultimately alienation. Youth ministries can therefore not function effectively without an integrated ministry, which includes the parental home. With all the challenges threatening their capacity, the parental home can also not function effectively as faith mediators without an inclusive youth ministry. The research thus clearly indicates that Nel’s theory of inclusive youth ministry, is not only noteworthy, but it is also in the long term, necessary to work towards the congregation’s eschatalogical sustainability.